Kewenangan Bawaslu Dalam Menangani Pelanggaran Pemilu Pasca Penetapan Hasil Pemilu Secara Nasional: Telaah Siyasah Syar'iyyah - Sari, Anggita Ananda (Jurnal Al Tasyri'iyyah, 2023)
ABSTRACT The purpose of this research is to 1) find out the form of Bawaslu's authority in handling elections after the election results are determined nationally. 2) Knowing the Legal Certainty of Follow-Up of Bawaslu Decisions, 3) Knowing the critical analysis of siyasah syariyyah on the authority of Bawaslu. In answering these problems, the author uses a type of library research (Library research). The research approach uses syar'i normative and juridical normative. The author's references in this study used primary data sources, namely books and journals related to Bawaslu and Elections, while secondary data sources were obtained from the Al-Qur'an, hadith. This study collects data by quoting, adapting, and analyzing using normative descriptive analysis of literature that represents and has relevance to the issues discussed, then reviews and concludes. After holding a discussion regarding the Authority of Bawaslu in handling elections after the determination of the national election results, a discussion was obtained regarding 1) Bawaslu legally and convincingly has the authority to handle election violations after the determination of the results of the national election vote. 2) Knowing the Legal Certainty of Follow-Up of Bawaslu Decisions. 2) Article 461(6) states that Bawaslu issues a decision on an administrative case which then Article 462 states that "KPU, Provincial KPU, and Regency/Municipal KPU are required to follow up on the decision of Bawaslu, Provincial Bawaslu, and Regency/City Bawaslu no longer than 3 (three) ) working days from the date the decision was read. 3) That Bawaslu in siyasa syariyyah is part of the al-hisbah area. In fiqh siyasah, Al Muraqabah waal-taqwim according to awdah is the responsibility of the whole community to supervise the government as their responsibility for the mandate of the representatives given. The author hopes that the implications of this writing are that it can be a source of consideration for the government to resolve polemics regarding the authority of the Bawaslu after the election results are determined and afterward, it also provides legal certainty against the ambiguity of overlapping authorities between election organizers. Keywords: Bawaslu Authority,Violation, Electoral Determination